Chronic hepatitis C treated with peginterferon alfa plus ribavirin in clinical practice - Velosa, J (2013)
BACKGROUND/AIMS: The role of genotype and viremia were retrospectively evaluated on sustained virological response (SVR) rates in routine clinical practice. METHODOLOGY: From 1907 patients with chronic hepatitis C proposed for treatment, we analysed 1380 (1124 naive and 256 treatment-experienced) with complete follow-up. Genotype and HCV RNA quantification were assayed by commercial tests. Viremia was considered high if >800,000IU/mL, and low if <400,000IU/mL. Liver fibrosis was staged in 614 patients. RESULTS: Genotype 1 was the most frequent (60%), followed by 3 (25%), 4 (9%) and 2 (2%); 3.2% had other or unclassified genotype. Genotype 1 was more prevalent in central Portugal and genotype 4 in the south. Viremia was =800,000IU/mL in 54.6% and <400,000IU/mL in 34.6% of the patients, particularly in genotype 2 (p<0.03) and 4 (p<0.001). Genotype non-1 had a significantly lower viral load (p=0.004). Mild or moderate fibrosis was present in 71.7% and bridging fibrosis or cirrhosis in 28.3%, with no differences among genotypes. Treatment was discontinued in 19.8%. SVR was achieved in 55.3% of naive and 36.3% of re-treated patients. CONCLUSIONS: Standard treatment of chronic hepatitis C in real-life achieves similar results obtained in clinical trials, despite differences of demographic and viral parameters.